Pyrromethene derivatives in three-component photoinitiating systems for free radical photopolymerization - Tarzi, Olga Inés (2010)
1,3,5,7,8-pentamethyl pyrromethene difluoroborate complex (HMP) and 2,6-diethyl-8-phenyl-1,3,5,7-tetramethylpyrromethene difluoroborate complex (EPP) were used to initiate the polymerization of a diacrylate in a two- and a three-component photoinitiating system (PIS), together with an amine (ethyl-4-dimethylaminobenzoate, EDB) and triazine A (2-(4methoxyphenyl)-4,6- bis(triehloromethyl)-1,3,5-triazine, TA) as coinitiators. For both pyrromethene dyes, the highest conversion was achieved with the three-component PIS. As these dyes have high-fluorescence quantum yields, steady state and time-resolved techniques were used to study the possible fluorescence quenching by the amine and the triazine, as well as laser flash photolysis to investigate the electron transfer process that occurs in these PIS from either the singlet or triplet excited states. The electron transfer reaction is evidenced by using time-resolved photoconductivity. Experiments show that the main interaction between the dye and both coinitiators is through its excited singlet state and the process is more efficient when TA is present. The beneficial effect noted when both coinitiators are used in a three-component system is ascribed to secondary reactions between the coinitiators and intermediates that lead to the generation of higher amount of initiating species and the recovery of the initial dye.